Development of Technology-Information-Based Businesses for Borokah Herbal Drink and UD Mela Jaya Fish Crackers in Nogosari Village, Pacet District, Mojokerto Regency - Adityo, R Dimas; Syafi’i, Syafi’i; Ekantoro, Julyantoro; D.F , Fernando Yunianda; Sanggraloka, Bima (STMIK Widya Cipta Dharma, 2025)
This community service project focuses on empowering two micro, small, and medium enterprises (MSMEs) in Nogosari Village, Pacet District, Mojokerto Regency: Jamu Herbal Barokah and UD Mela Jaya, a traditional fish cracker producer. Both enterprises face significant challenges in management and marketing, primarily due to limited financial literacy, lack of business administration systems, and minimal utilization of digital technology. The project aims to enhance their competitiveness and sustainability through the implementation of information technology-based solutions. These include the development of simple digital applications for financial recording and production management, as well as the adoption of digital marketing strategies using social media, marketplaces, and websites. Training and mentoring sessions are conducted to improve partners’ capacity in business management, financial documentation, and digital branding. The program aligns with Indonesia’s Asta Cita agenda and the Sustainable Development Goals (SDGs), particularly Goal 8—Decent Work and Economic Growth. Through the integration of information technology, the project promotes inclusive local economic growth, increases employment opportunities, and strengthens the independence of local entrepreneurs. Expected outcomes include improved business governance, wider market reach, and enhanced digital literacy among MSME actors, serving as a model for sustainable rural economic development based on local potential.